PENGARUH GAYA MENGAJAR DOSEN, ASISTENSI DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR APLIKASI AKUNTANSI PEMERIKSAAN - Popi Doni Irwanto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
Purpose of this research to knows the effect of the style of teaching, assistance and learning facilities to learning achievement accounting application inspection. This study is a survey on students who have finished take accounting applications inspection. A sample of 33 students with purposive random sampling technique. Sources of data used primary data and secondary data. Data collection techniques used questionnaires and documentation. Data was analyzed used multiple linear regression, F test, t test, the coefficient of determination. The survey results revealed that the style of teaching has effect positive and significant on learning achievement accounting application inspection. Assistance has effect positive but not significant positive on learning achievement accounting application inspection. Learning facilities has effect positive and significant on learning achievement accounting application inspection. Style of teaching, assistance and learning facilities affect the learning achievement accounting application inspection simultaneously. Style of teaching, assistance and learning facilities affect the learning achievement in the application of accounting examination was 28.6 percent, while the remaining 71.4 percent is influenced by other variables not studied, for example, is the motivation to learn and peer influence. Keywords: style of teaching, assistance, learning facilities, learning achievement